EXISTENCE OF CLASSICAL SOLUTIONS IN THE EINSTEIN-SKYRME MODEL - Syahreza Fadhilla, Emir
The interaction between scalar fields and gravity within Einstein’s General Theory of Re- lativity is a widely studied topic due to its applications in the effective modelling of stars